Zerit - Rosenthal, Jean, active 2017, (SAGE Knowledge. Cases., 2017)
In 2001, Jon Soderstrom, Director of Yale's Office of Cooperative Research, found himself in the midst of a maelstrom of negative publicity. Yale's patent on the drug Zerit had become the target of international activists and campus protests. Protestors asserted that the patent and Yale's licensing of the pharmaceutical to Bristol-Myers Squibb (BMS) was preventing low-cost generics from reaching millions suffering from HIV/AIDS in South Africa. After a meeting between Soderstrom and BMS, BMS lowered the price of Zerit in South Africa and other developing countries and the crisis cooled. But student protestors and others continued to question university policy on the use of patents in the development of new pharmaceuticals, the close relationship between big pharma and universities, and the ethics and goals of university research.